Determinants of perceived health and unmet healthcare needs in universal healthcare systems with high gender equality - Christina P. Tadiri; Teresa Gisinger; Alexandra Kautzky-Willer; Karolina Kublickiene; Maria Trinidad Herrero; Colleen M. Norris; Valeria Raparelli; Louise Pilote; on behalf of the GOING-FWD Consortium (BMC, 2021)
Abstract Background Patient attitudes about health and healthcare have emerged as important outcomes to assess in clinical studies. Gender is increasingly recognized as an intersectional social construct that may influence health. Our objective was to determine potential sex differences in self-reported overall health and access to healthcare and whether those differences are influenced by individual social factors in two relatively similar countries. Methods Two public health surveys from countries with high gender equality (measured by UN GII) and universal healthcare systems, Canada (CCHS2014, n = 57,041) and Austria (AT-HIS2014, n = 15,212), were analysed. Perceived health was assessed on a scale of 1 (very bad) to 4 (very good) and perceived unmet healthcare needs was reported as a dichotomous variable (yes/no). Interactions between sex and social determinants (i.e. employment, education level, immigration and marital status) on outcomes were analysed. Results Individuals in both countries reported high perceived health (Scoring > 2, 85.0% in Canada, 79.9% in Austria) and a low percentage reported unmet healthcare needs (4.6% in Canada, 10.7% in Austria). In both countries, sex and several social factors were associated with high perceived health, and a sex-by-marital status interaction was observed, with a greater negative impact of divorce for men. Female sex was positively associated with unmet care needs in both countries, and sex-by-social factors interactions were only detected in Canada. Conclusions The intersection of sex and social factors in influencing patient-relevant outcomes varies even among countries with similar healthcare and high gender equality.